2003
DOI: 10.1097/01.ju.0000049198.53424.1d
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral Stent Symptom Questionnaire: Development and Validation of a Multidimensional Quality of Life Measure

Abstract: Indwelling ureteral stents have a significant impact on health related quality of life. The new USSQ is a valid and reliable instrument that is expected to become a standard outcome measure to evaluate the impact and compare different types of stents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
290
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 378 publications
(303 citation statements)
references
References 18 publications
7
290
0
6
Order By: Relevance
“…Since a perfect ureteral stent that does not cause discomfort remains elusive, a fast and efficient approach to relieve stent-related symptoms is required (9). Joshi et al (5) developed the Ureteral Stent Symptom Questionnaire (USSQ) in order to evaluate the symptoms and impact on the quality of life of patients following ureteral stents, which included 38 scoring items over six sections, covering: Urinary symptoms, pain, general health, work performance, and sexual matters with additional problems. Additional methods, including the Visual Analog Pain Scale (VAPS), International Prostate Symptom Score (IPSS) and the Short-form 36 Health Survey Scale (SF-36) α 1 -blockers for the reduction of ureteric stent-related symptoms: A systematic review and meta-analysis have been applied to evaluate USS in relevant studies (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Since a perfect ureteral stent that does not cause discomfort remains elusive, a fast and efficient approach to relieve stent-related symptoms is required (9). Joshi et al (5) developed the Ureteral Stent Symptom Questionnaire (USSQ) in order to evaluate the symptoms and impact on the quality of life of patients following ureteral stents, which included 38 scoring items over six sections, covering: Urinary symptoms, pain, general health, work performance, and sexual matters with additional problems. Additional methods, including the Visual Analog Pain Scale (VAPS), International Prostate Symptom Score (IPSS) and the Short-form 36 Health Survey Scale (SF-36) α 1 -blockers for the reduction of ureteric stent-related symptoms: A systematic review and meta-analysis have been applied to evaluate USS in relevant studies (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…They found that ureteral stents are associated with significant symptoms, such as pain affecting daily activities (80%), urinary symptoms (73%), and reduced work capacity (58%), which reduce quality of life. During the research, it became clear that stents profoundly affect physical and psychosocial health and have a negative impact on functional capacity and work performance [3,5]. In our present study involving 117 patients, we did not find significant difference between the three groups concerning flank pain, hematuria, fever, and urinary tract infection.…”
Section: Discussionmentioning
confidence: 37%
“…It is a routine justified by the belief that this practice decreases ureteral stricture formation, protects the kidney, and minimizes postoperative pain [2]. However the use of stents is accompanied by significant morbidity, including pain, infection, and irritative voiding symptoms [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Üreteral stentlerin hayat kalitesini düşürdüğünü ve günlük yaşamı etkileyebilecek düzeyde ağrı (%80), üriner semptomlar (%73), çalışma gücünün kaybına (%58) yol açtıklarını saptamışlar-dır. Sonuç olarak stentlerin fiziksel ve psikolojik sağlığı etkilediği; fonksiyonel kapasite ve çalışma performansına negatif etkisi olduğu raporlanmıştır (5,12). Diğer taraftan El Harrech ve ark'ları, üreteroskopi yapılan 117 hastayı aldıkları çalış-malarında hastaları 3 gruba ayırarak değerlendirmişlerdir.…”
Section: Tartışılması Gereken Noktalarunclassified
“…Ancak stent yerleştirilmesi ağrı, enfeksiyon ve alt üriner sistem semptomları nedeniyle hastaların hayat kalitesini düşürmektedir (5,6). Ayrıca stentle ilişkili nadir komplikasyonlar olan stentin enkrustasyonu ve taşlaşması ve buna bağlı olarak üst ve alt üriner sistem enfeksiyonları görülebil-mektedir (7).…”
unclassified